2020
DOI: 10.1073/pnas.2002672117
|View full text |Cite
|
Sign up to set email alerts
|

JNK-mediated disruption of bile acid homeostasis promotes intrahepatic cholangiocarcinoma

Abstract: Metabolic stress causes activation of the cJun NH2-terminal kinase (JNK) signal transduction pathway. It is established that one consequence of JNK activation is the development of insulin resistance and hepatic steatosis through inhibition of the transcription factor PPARα. Indeed, JNK1/2 deficiency in hepatocytes protects against the development of steatosis, suggesting that JNK inhibition represents a possible treatment for this disease. However, the long-term consequences of JNK inhibition have not been ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 55 publications
0
48
1
Order By: Relevance
“…The Jnk hepa mice, in a C57BL/6J background, were generated as previously described (19,20). At 14 days of age mice received 25mg/kg (i.p.)…”
Section: Mouse Modelsmentioning
confidence: 99%
“…The Jnk hepa mice, in a C57BL/6J background, were generated as previously described (19,20). At 14 days of age mice received 25mg/kg (i.p.)…”
Section: Mouse Modelsmentioning
confidence: 99%
“…We identified these cysts as focal dilated duct structures which were morphologically connected and originated from the intrahepatic bile duct system. Of note, we could not detect neoplastic or dysplastic areas, arguing against the development of an intrahepatic cholangiocarcinoma (iCCA) or any iCCA precursor lesions ( 37 ). The cyst fluid of JNK1/2 LPC-KO mice contained a serum-like protein pattern, which is similar to a protein profile found in human biliary cysts ( 14 ).…”
Section: Discussionmentioning
confidence: 69%
“…Acute ethanol loading causes oxidative stress and activates cell-death signaling through the JNK pathway in the liver ( 31 ). In addition, JNK is a key mediator in hepatic steatosis, where it regulates transcription factor activity associated with lipid metabolism ( 32 , 33 ). In the present study, the upregulation of serum ALT and AST levels after ethanol treatment indicated hepatocytes damage.…”
Section: Resultsmentioning
confidence: 99%
“…JNK activation can cause programmed cell death, and increases the expression of lipogenic transcription factor sterol regulatory element binding protein (SREBP)-activated lipid synthesis enzymes, resulting in hepatic steatosis ( 31 , 33 , 40 , 41 ). Additionally, JNK may suppress hepatic peroxisome proliferator-activated receptor-α (PPAR-α) activation, which is a transcription factor and a positive regulator of intracellular free fatty acid and TG metabolism by regulating gene transcription involved in fatty acid transport and degradation in mitochondria and peroxisomes ( 32 ). Therefore, hepatic JNK activation increases oxidative stress, leads to hepatocyte apoptosis and injury, and contributes to hepatic steatosis via modulating lipid metabolic transcription factor activation.…”
Section: Discussionmentioning
confidence: 99%